Association between Serum Magnesium Level with Acute Coronary Syndrome (ACS) in Diabetes Mellitus (DM) Patients - Wulansari, Ratih; Soelistijo, Soebagijo Adi; Lefi, Achmad (Biomolecular and Health Science Journal, 2019)
Introduction: Until now, cardiovascular complications are still the highest cause of death and disability in DM patients. Hypomagnesemia in DM accelerate atherosclerosis and can cause instability and plaque rupture which can lead to acute coronary syndrome.Methods: Design of this study was observational analytic using a "case control" study involved 76 samples of DM patients, consisting of 38 samples with SKA (+) and 38 samples with SKA (-). Subjects of this study were all DM patients in the period July-December 2018 in the Emergency Room (ER) and Outpatient Installation of Endocrine at the RSUD Dr. Soetomo Surabaya, which fulfills the criteria for inclusion and exclusion. Demographic data and clinical characteristics are presented descriptively. If data is normally distributed then an unpaired t test is carried out and if the data is not normally, distributed with Mann Whitney test is performed. The statistical test was stated to be significant if p <0.05. The association between hypomagnesemia and the incidence of ACS a multivariate logistic regression test was performed, the risk number was in the form of odds ratios (OR). Results: This study involved 76 subjects with diabetes mellitus with SKA and non SKA 38 subjects. The mean serum magnesium level in the ACS group was lower than non ACS (1.9 mg / dL vs. 2.1 mg / dL), hypomagnesemia cut-off of <2.08 mg / dL. In this study hypomagnesemia as a risk factor for the incidence of ACS in DM patients with OR 2.8 (CI 1.1-7.6; p = 0.039).Conclusion: Magnesium levels in the ACS group were lower than the non ACS group. Hypomagnesemia Increase The Incidence of Acute Coronary Syndrome in Diabetes Mellitus Patients.